2007
DOI: 10.1111/j.1468-1293.2007.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Nevirapine‐associated toxicity in HIV‐infected Thai men and women, including pregnant women

Abstract: ObjectivesThe aim of the study was to determine the incidence of, and risk factors for, nevirapine (NVP)-associated hepatotoxicity and rash in HIV-infected Thai men and women, including pregnant women, receiving NVP-containing highly active antiretroviral therapy (HAART). MethodsNVP-containing HAART was prescribed to eligible men and women enrolled in the Prevention of Mother-To-Child Transmission of HIV (PMTCT) and MTCT-Plus programmes. All pregnant women received zidovudine (ZDV)/lamivudine (3TC)/NVP from 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
4
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 39 publications
(80 reference statements)
6
38
4
2
Order By: Relevance
“…Participants with hepatitis B or C infection were excluded from 2 studies, 4,27 whereas 7 studies reported the prevalence of hepatitis co-infection. [28][29][30]34,[36][37][38] NVP was initially commenced at 200 mg daily for 14 days in all women. The CD4 cut-off was 250 cells/µl for toxicity analyses in all studies, except for one (CD4 cut-off of 200 cells/ µl).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants with hepatitis B or C infection were excluded from 2 studies, 4,27 whereas 7 studies reported the prevalence of hepatitis co-infection. [28][29][30]34,[36][37][38] NVP was initially commenced at 200 mg daily for 14 days in all women. The CD4 cut-off was 250 cells/µl for toxicity analyses in all studies, except for one (CD4 cut-off of 200 cells/ µl).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies with CD4 cut-offs of 500 29 Fourteen studies were reviewed, including a total of 2 663 participants (Table 2). 4,5,[27][28][29][30][31][32][33][34][35][36][37][38] One study was funded by the NVP manufacturer Boehringer Ingelheim. 30 The studies, mostly undertaken between 2001 and 2006, were predominantly observational with participant numbers ranging from 17 to 703.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1e4,6,8,9 Only one study, performed in Asian patients, reported a substantially higher rate of hepatotoxicity (15.6%) in pregnant women using NVP. 7 This study however had only a small proportion of patients tested for HBV or HCV, and the presence of a coinfection in this study may have added to the high percentage of hepatotoxicity, as HIV-positive Asian communities were found to have a high prevalence of HCV. 13 cART in pregnant and non-pregnant womenCoinfection with HBV or HCV has been reported to be an independent risk factor for antiretroviral-associated hepatotoxicity, including NVP-related hepatotoxicity.…”
Section: Hepatotoxicitymentioning
confidence: 99%
“…Several European researchers reported no relationship between a high CD4 count and side effects. 27,33,34 Among pregnant women, reports from Mozambique, 21 Brazil, 32 Ireland, 34 Thailand, 35 and United States 36 describe a high risk to develop side effects if NVP is started at a high CD4 count, but other reports found not such relationship. [37][38][39] Based on our findings, we have found no evidence that the FDA warning is warranted to the population studied here.…”
Section: Discussionmentioning
confidence: 91%